The Next-Generation Shopper: A Study of Generation-Z Perceptions of AI in Online Shopping - Ovidiu-Iulian Bunea; Răzvan-Andrei Corboș; Sorina Ioana Mișu; Monica Triculescu; Andreea Trifu (Journal of Theoretical and Applied Electronic Commerce Research)
This study explores the impact of artificial intelligence (AI) tools on the purchase intentions of members of Generation Z (Gen Z) in online shopping, using an adapted technology acceptance model (TAM). It incorporates exposure to AI, usage of AI, and knowledge about AI, alongside the existing TAM parameters of perceived usefulness of AI (PUAI) and perceived ease-of-use of AI (PEUAI). A 38-item questionnaire was distributed, yielding data from 1128 Gen Z respondents. Partial least squares structural equation modeling (PLS-SEM) and importance–performance analysis (IPA) were applied to examine the hypothesized relationships. The study identified significant direct effects of exposure, use, and knowledge on PUAI and PEUAI, and that these effects affected consumers’ purchase intentions. Indirect effects analysis revealed that PUAI and PEUAI mediate between AI exposure, use, knowledge, and purchase intentions, suggesting that greater understanding of and familiarity with AI enhance the propensity to engage in AI-powered online transactions. The ease of integrating AI into daily life and perceived AI utility enhance purchase intentions. The study offers insights for online retailers leveraging AI technologies in an effort to enhance consumer purchase experiences, emphasizing the potential of AI to positively influence choices while enhancing trust, familiarity, and the overall user experience.